2018
DOI: 10.1186/s12882-018-1084-1
|View full text |Cite
|
Sign up to set email alerts
|

Star fruit nephrotoxicity: a case series and literature review

Abstract: BackgroundStar fruit is a popular medicinal fruit in the tropics. Its hypoglycaemic properties are considered useful in achieving glycaemic control in diabetes. Star fruit induced nephrotoxicity is a rare cause of acute kidney injury in individuals with both normal and reduced baseline renal function. We present three cases of acute kidney injury due to star fruit nephrotoxicity from Sri Lanka, and discuss the published literature on this topic.Case presentationThree Sri Lankan patients, all with a background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Patients who live in tropical areas are prohibited from eating carambolas, also known as star fruit, given the accumulation of toxic substances. 16 …”
Section: Why Is It Important To Follow the Recommended Diet During Thmentioning
confidence: 99%
“…Patients who live in tropical areas are prohibited from eating carambolas, also known as star fruit, given the accumulation of toxic substances. 16 …”
Section: Why Is It Important To Follow the Recommended Diet During Thmentioning
confidence: 99%
“…Although prospective studies are lacking, a large number of case reports suggested a causative role of dietary oxalate on acute kidney injury. Star fruit-induced acute oxalate nephropathy is one of the most reported in literature [110][111][112][113]. A case series of 3 patients who presented with AKI after star fruit ingestion was recently published, suggesting the potential role of this fruit in inducing acute oxalate nephropathy in individuals with both normal and abnormal kidney function due to its high oxalate content [110], especially for fresh fruit juice (up to 829 mg/dL) [111].…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…Star fruit-induced acute oxalate nephropathy is one of the most reported in literature [110][111][112][113]. A case series of 3 patients who presented with AKI after star fruit ingestion was recently published, suggesting the potential role of this fruit in inducing acute oxalate nephropathy in individuals with both normal and abnormal kidney function due to its high oxalate content [110], especially for fresh fruit juice (up to 829 mg/dL) [111]. A reported case of AKI in an 81 years old man with CKD and diabetes showed biopsy-proven oxalate nephropathy thought to be from the consumption of large amounts of vitamin C and high oxalate foods [52].…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…Also, neurotoxicity performances ranged from hiccups to status epilepticus. The excessive uptake of A. carambola could lead to acute kidney injury, particularly in an empty stomach, or dehydration state, and the use of A. carambola as therapy for an elderly patient is not recommended on an empty stomach ( Wijayaratne et al, 2018 ). In addition, A. carambola has threatened people's health despite the relatively low frequency of star fruit intake.…”
Section: Toxicity Assessmentmentioning
confidence: 99%